Agomelatina em ratas: efeitos sobre comportamentos relacionados à ansiedade à luz do seu efeito antidepressivo - Gomes, Ana Clara da Costa Nunes (2019)
Agomelatine is a MT1 and MT2 receptors agonist and 5-HT2C receptor antagonist used in the pharmacotherapy of depressive disorders. In addition, its use has been suggested to relieve symptoms of anxiety disorders, including panic attacks. The aim of present study was to evaluate if agomelatine administration alters anxiety and panic-related responses in female rats. Wistar rats were submitted to two tests of anxiety based on innate aversion of rodent to open and unprotected places, the elevated plusmaze (EPM), the elevated T-maze (ETM) and to the open field test (OF), the latter to evaluate indices of anxiety and the locomotor activity of the rats. In our results, twe observed that there were no changes in the locomotor activity of the females submitted to the oral administration of agomelatine in short term (25, 50 or 75 mg/kg, 60 minutes before the test), as assessed in the open field test and EPM. Regarding anxiety-like responses, the administration of agomelatine (12.5, 25 or 50 mg/kg, 60 minutes before the test) did not alter the exploration of the EPM. In ETM, agomelatine administred sixty minutes before the pre-test and test sessions did not modify the inhibitory avoidance acquisition or escape response at doses of 50 and 75 mg/kg. However, the dose of 25 mg/kg favored a reduction in latency to the escape, suggesting a panicogenic-like effect. In the absence of efficacy of short-term administration of agomelatine on experimental anxiety, and in order to confirm its antidepressive efficacy in females, the rats submitted to ETM have been submitted to administration of the same doses of agomelatine previous 60 minutes to OF, pretest and forced swimming test (FST), with a 24-hour interval between procedures. In FST, administration of agomelatine (50 and 75 mg/kg) did not alter climbing behavior, but reduced immobility time, thus reinforcing in females the antidepressant-like profile of this drug. Thus, in order to verify whether longterm administration of agomelatine would favor an anxiolytic and/or panicolytic effect, an independent rat group was administered for 25 days agomelatine at a dose of 50 mg/kg and, 60 minutes after the last administration, to the ETM, OF and blood test for biochemical (AST and ALT) and histological analysis of the liver. The long-term administration of agomelatine did not change any of the parameters analyzed, suggesting the absence of behavioral effects and hepatotoxicity. The data obtained here show a lack of anxiolytic profile of agomelatine in short and long term, but confirm their antidepressant potential in the short term in females.